A Letter to My Son. Issue 4 (September 2022) - Scott, Dave
Abstract : This contribution to the theme of 'Scotland and the Two Irelands' takes the form of a letter from an Antrim-born father to his Scottish-born son. It offers an (autobiographical) account of the political changes in Scotland and Northern Ireland since the late 1990s, and outlines how it is the people we love that makes places home.